A critical overview of the current myofascial pain literature – July 2018. Issue 3 (July 2018) - Dommerholt, Jan; Finnegan, Michelle; Hooks, Todd; Chou, Li-Wei
Abstract: In the current issue of this clinical overview, we are pleased to include several basic research studies ranging from the differentiation of radicular and non-radicular low back pain based on the presence of trigger points (TrPs) to the role of TrPs in patients with osteoarthritis, the diagnostic criteria of TrP, the accurate placement of needles in the piriformis muscle with dry needling (DN), and the reliability of TrP identification, among others. As usual, there are many new DN studies, but also several review papers, and manual TrP research. Contributing authors come from as many as 15 different countries!